Posterior Urethral Valve Patients’ Presentation with and without Deranged Renal Function - Irshad Khan, Sami Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Posterior Urethral Valve (PUV) is a congenital anomaly affecting the male urinary tract, leading to urinary tract obstruction that can cause severe renal complications, including hydronephrosis, renal damage, and, if untreated, chronic kidney disease (CKD) or end-stage renal disease (ESRD). PUV is the most common cause of lower urinary tract obstruction in male newborns, with clinical manifestations varying according to the severity of the condition. Early diagnosis and timely intervention are essential for improving outcomes in these patients. Objective: This study aims to evaluate the clinical presentation, diagnostic features, renal function outcomes, and the impact of early treatment on preventing renal damage progression in PUV patients. The study focuses on the relationship between age at presentation, clinical symptoms, and the degree of renal dysfunction. Methods: This retrospective study was conducted at Khyber Teaching Hospital (KTH) Peshawar from 2018 to 2020, involving 50 paediatric patients diagnosed with PUV. The patients were divided into two groups: those with deranged renal function (n=30) and those without (n=20). Data collected included age at presentation, clinical symptoms, imaging findings (such as hydronephrosis and renal pelvicalyceal dilation), serum creatinine levels, glomerular filtration rate (GFR), and treatment strategies. The effects of valve ablation, dialysis, and supportive care on renal function were also assessed. Results: The study revealed significant differences between the two groups. Patients with deranged renal function presented at a later age (mean age 2.5 years) and exhibited more severe clinical symptoms, including oliguria (85%), abdominal distension (60%), recurrent urinary tract infections (70%), and poor growth (50%). In contrast, those without renal dysfunction presented earlier (mean age 1.5 years) with mild symptoms and normal urinary output. Severe hydronephrosis (Grade III-IV) was observed in 85% of the deranged renal function group, compared to mild-to-moderate hydronephrosis (Grade I-II) in 40% of the non-renal dysfunction group. Elevated serum creatinine levels (>1.5 mg/dL) were found in 90% of patients with renal dysfunction, while 95% of the non-renal dysfunction group had normal creatinine levels. Early intervention with valve ablation, supported by additional treatments like catheterization or dialysis in severe cases, contributed to improved outcomes in the non-renal dysfunction group, with 90% achieving stable renal function. Conclusion: The study highlights the crucial role of early diagnosis and intervention in PUV patients. Those with deranged renal function present later and suffer from more severe clinical symptoms and complications. Timely valve ablation and supportive care significantly improve outcomes, preventing the progression to CKD or ESRD. Early intervention is essential for achieving favourable renal outcomes and preventing long-term renal damage in these children. Keywords: Posterior Urethral Valve, Renal Dysfunction, Kidney Function, Diagnosis, Early Treatment, Age at Presentation, Chronic Kidney Disease, Paediatric Urology.